Bridging the gap between research and clinical care: strategies to increase staff awareness and engagement in clinical research. (March 2022) - Shepherd, Maggie; Endacott, Ruth; Quinn, Helen
Background: Research active hospitals have better patient outcomes and improvements in healthcare are associated with greater staff engagement in research. However, barriers to research activity include inadequate knowledge/training and perceptions that research is a specialist activity. Nursing is an academic discipline but the infrastructure supporting nursing research worldwide is variable and sustaining clinical academic careers remains challenging. The National Institute of Health Research 70@70 Senior Nurse Research Leader programme provides dedicated time to increase clinical academic opportunities and foster a research culture across England; we describe initiatives developed by one National Institute of Health Research 70@70 leader to increase clinical staff engagement in research. Aim: The purpose of this work was to develop initiatives to facilitate clinical research opportunities and bridge the gap between clinical care and research. Methods: New strategies were developed in one health service to increase clinical staff engagement in research activity. This included: (a) Chief Nurse Research Fellows: clinical staff undertaking bespoke research training to identify local clinical research priorities, (b) an exemplar nurse-led Embedding Research In Care unit to pioneer innovation, evaluation and research participation supported by a research facilitator and (c) a Clinical Academic Network for nursing, midwifery and allied healthcare professionals to aid collaborative working. Results: The first cohort of Chief Nurse Research Fellows have successfully completed a bespoke training programme and, with mentoring, developed projects to tackle clinical problems. The Embedding Research In Care unit initiative was configured and the first Embedding Research In Care unit has been awarded. A Clinical Academic Network group of 25+ nurses, midwives and allied health professionals was established and provides peer support and mentoring. Conclusions: This multi-faceted approach has successfully supported research training/engagement, enabled career development and identified nurses/midwives with potential to undertake clinical academic careers. A range of strategies, such as those described in this paper, are required to successfully bridge the gap between clinical care and research and provide additional opportunities for clinical staff to become engaged in a research active career.